1988
DOI: 10.1038/icb.1988.49
|View full text |Cite
|
Sign up to set email alerts
|

A single dose of UV radiation suppresses delayed type hypersensitivity responses to alloantigens and prolongs heart allograft survival in mice

Abstract: Summary The systemic effect of ultraviolet (UV) irradiation on delayed type hypersensitivity (DTH), contact hypersensitivity (CHS) and allograft rejection was investigated in BALB/c mice which had been exposed to a single 1 h treatment with UV radiation (27 kJ/m^) from FS40 sunlamps (60% UVB). After UV irradiation (3-5 days), mice were treated on an unirradiated site with either a subcutaneous injection of allogeneic spleen cells or a topical application of the contact scnsitizer oxazolone (OX). The DTH respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
3
21
1
Order By: Relevance
“…The number of ISC in the head kidney, a major immunoglobulin-synthesizing organ in fish, did not change as a result of the UV treatment. This suggests that it was mainly T-cell responses that were affected by UVB irradiation here, which is consistent with the results of mammalian studies (25,60).…”
Section: Lymphocyte Functions and Plasma Igmsupporting
confidence: 91%
See 1 more Smart Citation
“…The number of ISC in the head kidney, a major immunoglobulin-synthesizing organ in fish, did not change as a result of the UV treatment. This suggests that it was mainly T-cell responses that were affected by UVB irradiation here, which is consistent with the results of mammalian studies (25,60).…”
Section: Lymphocyte Functions and Plasma Igmsupporting
confidence: 91%
“…The main targets of UVB are the T-cell-mediated immune functions, e.g. delayed-type hypersensitivity and allograft rejection (25). A compromised immune defense against infections (26) and malignant tumors (27) has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This suppression differs from the short‐term suppression observed in adults following UVR exposure. In contrast to neonatal UVR exposure where suppression is apparent at 8 weeks, studies in adult mice have shown suppression for only up to 2 weeks post‐irradiation 23 , 49 . In addition, the level of suppression observed in this study was lower than observed in adult studies.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation of mice with ultraviolet B (UVB; 290-320 nm) initiates a suppression of delayed-type hypersensitivity (DTH) and contact hypersensitivity (CHS) responses (Giannini 1986;Howie et al 1986;Mottram et al 1988;Noonan et al 1981a;Streilein and Bergstresser 1988;Yasumoto et al 1987) which is both dose and wavelength dependent (De Fabo and Noonan 1983;Noonan et al 1981 a). Immunosuppression occurs with biologically relevant doses of UVB which are readily available from natural sunlight ).…”
Section: Introductionmentioning
confidence: 99%